2002
DOI: 10.1021/ar010072a
|View full text |Cite
|
Sign up to set email alerts
|

Solid Acids for Green Chemistry

Abstract: Solid acids and especially those based on micelle-templated silicas and other mesoporous high surface area support materials are beginning to play a significant role in the greening of fine and speciality chemicals manufacturing processes. A wide range of important organic reactions can be efficiently catalyzed by these materials, which can be designed to provide different types of acidity as well as high degrees of reaction selectivity. The solid acids generally have high turnover numbers and can be easily se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
346
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(350 citation statements)
references
References 25 publications
1
346
0
3
Order By: Relevance
“…Mineral acids are among the most ubiquitous catalysts in industry but their corrosion and toxicity problems have prompted to the search for recoverable and reusable heterogeneous acid catalysts [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral acids are among the most ubiquitous catalysts in industry but their corrosion and toxicity problems have prompted to the search for recoverable and reusable heterogeneous acid catalysts [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Brown and Hargreaves in 1999 noted that the introduction of super acidity on acids improves its activity and increases its selectivity [91]. The successful inclusion of the sulfate group on the zirconia skeleton has improved its application which has projected sulfated zirconia as a potential particle of great importance in many reactions, which tends to be improved when the size of the sulfated zirconia is reduced to nanosize [92,93]. The antioxidant, antibacterial, and antitumor potentials of sulfated zirconia have been investigated and reported recently [8], which opened the way for more studies on the other applications of the sulfated zirconia in nanosize for pharmacological benefits.…”
Section: Zirconia Nanoparticlesmentioning
confidence: 99%
“…Clark showed that the catalytic activity of silica supported AlCl 3 arose from Lewis acid activation of the Brønsted acidic site on the silica surface (Figure 2). 3 Classic acid catalyzed reactions, such as the addition of HCl to alkenes, often show a second order dependence on the acids. In that sense, the involvement of dimeric acids such as HCl HCl might be speculated (Figure 3).…”
Section: Combined Acid Catalysismentioning
confidence: 99%
“…10 We found that the tricyclic ethers were obtained from geranyl phenyl ethers, o geranylphenols, and geranylacetone derivatives using (R) BINOL derivatives and SnCl 4 . The reaction proceeded smoothly even in catalytic amounts of the chiral LBA and often took place via [1,3] Claisen type rearrangements using geranyl phenyl ethers as substrates. The best result of 90% ee was observed for the cyclization of p bromophenyl geranyl ether.…”
Section: Lewis Acid Assisted Brønsted Acid Catalysts (Lbas)mentioning
confidence: 99%